Let's explore carrots! - Colella, Jill (2021)
"Carrots have a mild, sweet flavor, making them popular to eat. Inspire food literacy with photos and text that show how carrots grow, how to roast them, and how to grow carrot tops"--
All about carrots -- Let's compare -- Let's explore -- Let's dig up carrots -- Let's cook -- Let's make.
Includes bibliographical references and index.
Ages 4-8
Grades K-1
Keywords: Carrots -- Juvenile literature